Expensive Egos: Narcissistic Males Have Higher Cortisol - Reinhard, David A.; Konrath, Sara H.; Lopez, William D.; Cameron, Heather G. (PloS one, 2012)
Narcissism is characterized by grandiosity, low empathy, and entitlement. There has been limited research regarding the hormonal correlates of narcissism, despite the potential health implications. This study examined the role of participant narcissism and sex on basal cortisol concentrations in an undergraduate population. Participants were 106 undergraduate students (79 females, 27 males, mean age 20.1 years) from one Midwestern and one Southwestern American university. Narcissism was assessed using the Narcissistic Personality Inventory, and basal cortisol concentrations were collected from saliva samples in a laboratory setting. Regression analyses examined the effect of narcissism and sex on cortisol (log). There were no sex differences in basal cortisol, F(1,97) = .20, p = .65, and narcissism scores, F(1,97) = .00, p = .99. Stepwise linear regression models of sex and narcissism and their interaction predicting cortisol concentrations showed no main effects when including covariates, but a significant interaction, β = .27, p = .04. Narcissism was not related to cortisol in females, but significantly predicted cortisol in males. Examining the effect of unhealthy versus healthy narcissism on cortisol found that unhealthy narcissism was marginally related to cortisol in females, β = .27, p = .06, but significantly predicted higher basal cortisol in males, β = .72, p = .01, even when controlling for potential confounds. No relationship was found between sex, narcissism, or their interaction on self-reported stress. Our findings suggest that the HPA axis is chronically activated in males with unhealthy narcissism. This constant activation of the HPA axis may have important health implications.